(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
As Kaikovus himself pointed out, a whole work is dedicated to the education of young men described in the last chapter. Kaykovus said "... I wrote all my thoughts and concepts in a book for you, and I knew every science, every craft and every fish , I explained them all in forty-four chapters", the life experience of every young person’s mental, moral, and physical education. described the ways and methods of bringing to maturity in connection with .